1983
DOI: 10.1111/cge.1983.24.5.339
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of classic PKU in Italy estimated from consanguineous marriages and from neonatal

Abstract: As already described for cystic fibrosis and Friedreich ataxia, the incidence of PKU in Italy has been estimated by determining the increase of consanguineous marriages among 178 couples of PKU parents over the frequencies carefully established for the same marriages in the general Italian population for each of the 95 provinces during a 55-year period. The incidence estimated (between 1/15595 and 1/17815 according to two different formulas) is not very different from the incidence derived from screening progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
31
3

Year Published

1985
1985
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 1 publication
5
31
3
Order By: Relevance
“…The relatively small size of the sample of FA patients may be another source of error, but the number of cases col lected was similar or higher than in other studies (table 1). Possible heterogeneity of the series is also improbable because molecular studies have shown genetic homogeneity of FA patients diagnosed with the same criteria that we used [22], Our high incidence and prevalence figures are in consonance with the two Italian studies cited [16,21], In both instances the frequency of FA resulting from the consanguinity analy sis was higher than that obtained by direct studies. This may indicate a partial pene trance of the gene which is not known at present.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The relatively small size of the sample of FA patients may be another source of error, but the number of cases col lected was similar or higher than in other studies (table 1). Possible heterogeneity of the series is also improbable because molecular studies have shown genetic homogeneity of FA patients diagnosed with the same criteria that we used [22], Our high incidence and prevalence figures are in consonance with the two Italian studies cited [16,21], In both instances the frequency of FA resulting from the consanguinity analy sis was higher than that obtained by direct studies. This may indicate a partial pene trance of the gene which is not known at present.…”
Section: Discussionsupporting
confidence: 79%
“…Con sanguinity values which they obtained were underestimates, and they thought that these differences could be a consequence of genetic heterogeneity of the disease. Later Romeo et al [16] calculated the FA incidence in South ern Italy using the data on consanguineous marriages given by the Catholic church which had been previously reported by Moroni [21], Comparison of prevalence rates obtained by direct studies (table 1 ) was not consistent with the heterogeneity hypothesis. In Northern Ita ly, Leone et al [7] also compared real consan guinity rates and expected one according to prevalence data.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical phenotype observed in our FRDA patients was the typical one described in previous reports [2,3,11,23]. In Caucasians, birth FRDA incidence has been estimated at 1 in 22,000-36,000 [43][44][45], even though there are countries, like Finland, with a lower incidence [46]. The prevalence rate of the disease in Western countries appears to vary between 10 and 20 !…”
Section: Discussionsupporting
confidence: 77%
“…The accumulation of mutations in alleles in autozygous segments during recent generations thus makes it possible to identify the occurrence of new mutational events [29] . The analysis of disease-causing mutations in the children of consanguineous parents has additionally facilitated the calculation of reliable incidence estimates for autosomal recessive disorders [30][31][32][33] by essentially following the same strategy which in the pre-molecular era was based solely on demographic data [34][35][36][37] . During that earlier era, consanguineous marriages showed major variations in space and time for different populations.…”
mentioning
confidence: 99%